Effects of Acacia nilotica Leaf Extract on Adrenaline-induced Hyperlipidemia and Cardiac Remodeling in Rats (Bangladesh Pharmaceutical Journal, 2012)
Hyperlipidemia is one of the major causes of disability in western as well as in developing countries. The present study was designed to investigate the effect of the ethanolic leaf extract of a Bangladeshi medicinal plant Acacia nilotica (AN) on adrenaline-induced hyperlipidemia and cardiac remodeling in rats. The plant extract and commercial lipid lowering drug atorvastatine were administered in adrenaline-induced hyperlipidemic rats (AIHRs) through intraperitoneal route for one week at a dose of 30 mg and 0.04 mg per 150 gm body weight of rat, respectively. The AN extract showed a significant (P